HLA polymorphism in Sudanese renal donors - Ameer M Dafalla; D J McCloskey; Almutaz A Alemam; Amel A Ibrahim; Adil M Babikir; Nagla Gasmelseed; Mohamed El Imam; Ahmed A Mohamedani; Mubarak M Magzoub (Saudi Journal of Kidney Diseases and Transplantation, 2011)
The main objective of this study is to provide a database for renal transplantation in Sudan and to determine the HLA antigens and haplotype frequencies (HFs) in the study subjects. HLA typing was performed using the complement-dependant lymphocytotoxicity test in 250 unrelated healthy individuals selected as donors in the Sudanese Renal Transplantation Program. Considerable polymorphism was observed at each locus; A2 (0.28), A30 (0.12), A3 (0.09), A24 (0.09), A1 (0.09), and A68 (0.06) were the most frequent antigens in the A locus, while B51 (0.092), B41 (0.081), B39 (0.078), B57 (0.060), B35 (0.068), B 50 (0.053) and B 52 (0.051) were the most common B locus antigens. DR13 (0.444) and DR15 (0.160) showed the highest antigen frequencies (AFs) in the DR locus. In the DQ locus, DQ1 showed the highest gene frequency (0.498), while DQ2 and DQ3 AFs were (0.185) and (0.238), respectively. The most common HLA-A and -B haplotypes in positive linkage disequilibrium were A24, B38; A1, B7; and A3, B52. The common HLA-A and -B HFs in positive linkage disequilibrium in the main three tribe-stocks of the study subjects (Gaalia, Nile Nubian and Johyna) were A24, B38 for Gaalia; A24, B38 and A2, B7 for Johyna; and A2, B64 and A3, B53 for Nile Nubian. These results suggest that both class I and class II polymorphisms of the study subjects depict considerable heterogeneity, which reflects recent admixture of this group with neighboring Arabs and African populations.